Heat transfer enhancement of an internally and externally dimpled pipe heat exchanger – Numerical study. (2022) - Malapur, Harsh V.; Havaldar, Sanjay N.; Kharade, Utkarsha V.
Abstract: Many researchers have concentrated on employing dimpled pipes in heat exchanger designs to improve heating and cooling capabilities. Heat transfer increases with dimple protrusions on the inner and outer sides of a pipe in this simulated simulation. Protruding dimples in a helical pattern were modelled over the surfaces of the pipe heat exchanger, which had a constant pitch. Cold fluid (water) flows on the outside of the pipe, while the hot fluid (water) flows on the inside. The mass rate of fluid flow was varied for the dimpled pipe heat exchanger (along and opposite flow arrangement). In his research, heat transfer enhancement under varying flow conditions inside a pipe heat exchanger with spherical dimples on the pipe inside and on the outside (with varying helical pitch) is investigated numerically. The findings of the numerical study were used to determine various heat transfer characteristics for dimpled inside and outside pipe heat exchangers. It was discovered that adding dimples to pipe surfaces increased pressure loss for both hot and cold fluids. Dimples break the boundary layer in flow of the hot fluid when it encounters a dimple inside the pipe (hot fluid passage). Similarity, dimples break the boundary layer in flow of the cold fluid when it encounters a dimple on the outside of the pipe (cold fluid passage). It was discovered this phenomenon enhances the heat transfer coefficient between the hot and cold fluid in dimpled tube heat exchanger with dimples on the inside and on the outside. The heat transfer coefficient (overall) in internally and externally dimpled helical counter heat exchangers was found to be higher than in smooth counter heat exchangers under similar input and boundary conditions.